Effective Teaching in Schools : Theory and Practice - Kyriacou, Chris (Cheltenham Nelson Thornes, 2001)
Aims to bridge the gap between theory and practice, by considering what is involved in establishing and maintaining the effectiveness of an educational experience, both at the surface level of what the teacher needs to be doing, and at the underlying level of what psychological processes underpin this"--Introduction.
Include References and Index
Keywords: Classroom management